Border thinking and feminist solidarity in the fourth world - Nandorfy, Martha (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
From a governmental perspective, multiculturalism tends to be reduced to a hollow celebration of superficial differences, a strategic policy to control and contain forms of difference that actually require a process of community awareness to open towards the other, rather than merely tolerate it. This essay examines the writing of several Mexican-Americans and Chicano authors through the approach of their thought border. Gloria Anzaldúa’s and Cherrie Moraga’s poems illuminate perspectives of such conceptual strength as Chandra Talpade Mohanty’s most theoretical and academic discourse. The poets, performative artists and academics I consider in this work build intercultural bridges as solidary and collective response against commercial, military and government powers who speak of erasing borders when it comes to the free flow of money and hand cheap labor, but that want close them to prohibit the free flow of ideas and creative beings who seek a better life.